Quality Postharvest of Achillea millefolium L, Onganum vulgare L and Petroselinum crispum (Miller) AW. Hill in Three packaging (Revista Brasileira de Plantas Medicinais, 1999)
Most of the medicinal plants is marketed in the dehydrated form, what turns the processing fundamental postharvest for finish quality of the product. Oregano (Origanum vulgare L.), parsley (Petroselinum crispum (Miller) A.W. Hill), and yarrow (Achillea millefolium L.), were dehydrated in Dryness chamber (CS - Dryness chamber with relative humidity ranging from 50 to 60%); conditioned in glass recipients, or in polietileno of low density or in paper packaging and stored in Dryness chamber and in shut room (SF). The statistical method was randomized, with five repetitions, being the treatments arranged in the factor 3x3x2 The treatments were evaluated in three times: after one week, six months and an year of storage, through sensorial and microbiological analysis of the leaves of the species. It was venfied that the microbiological quality ol the plants did not showed statitical diferences after one week, however, after six months, to yarrow (1900 UFC/g) and the parsley (1840 UFC/g) they presented better microbiological charactenstc quality in CS in glass packing; the oregano maintained the characteristics so much in CS( 1660 UFC/g), as in Io SF(1700 UFC/g); in glass, polietileno After one year only the oregano maintained the desirable microbiological characteristic when packaging in polietileno and glass and stored in CS or SF, so that for the three species the largest contamination happened with the use of so much paper in CS or SF.